Training Load and Injury Incidence of Under-19, Under-21 and enior Netball Players - Colleen Sinclair; Derik Coetzee; Robert Schall (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Research demonstrated links between training load, performance adaptation and injury risk in sport. In netball, monitoring and optimising training load is essential to support player welfare and reduce injuries. The aim was to determine the training loads (session rating of perceived exertion X session duration) and injury incidence of under-19 (u/19), under-21 (u/21) and senior elite netball players in the Free State Province, South Africa. A descriptive cohort research was conducted. Weekly training monitoring and injury questionnaires were used. Thirty-six netball players (12 per age group) that participated in a competitive season were eligible. Data were collected over 12 consecutive weeks. In week 7, the University Sport South Africa (USSA) netball tournament took place, week 8 was university holidays and week 12 the National Netball Championships. Data for weeks 1–6 and 9–11 represented normal training weeks. Descriptive statistics were calculated per player, age group, and position. Significant differences in training load were found between age groups, with senior players recording notably lower loads than u/19 and u/21 players. No significant differences were observed between playing positions. Injured u/19 players consistently had higher training loads than their uninjured peers. Most injuries, predominantly ligamentous, occurred during matches. Age-related disparities in training load highlight the need for tailored workload strategies. Understanding position-specific and age-specific demands can aid coaches and strength and conditioning staff in optimising training loads to reduce injury risk and enhance performance.